Asuhan Keperawatan Diagnosa Hipertermi Pada Pasien Anak Demam Menggunakan Kompres Aloe vera Di RSUD Abdoel Wahab Sjahraine - maria katarina, maria; aries abiyoga , aries (Jurnal Perempuan dan Anak, 2025)
Background: Fever is a change from a healthy state to illness, which causes the body to react by increasing body temperature above the standard limit. One way to reduce fever is non-pharmacological, such as applying a compress and using the traditional Aloe vera plant. Aloe vera is known to be effective in reducing children's fever because the content in aloe vera can stimulate the hypothalamus to reduce body temperature. Purpose: This study aimed to see changes in the patient's body temperature before and after being given an aloe vera compress. Method: The method used in preparing this case study was to use a nursing process approach and describe the nursing care actions given to children with hyperthermia, starting from assessment, nursing diagnosis, intervention, implementation and evaluation. Results: Results were obtained after carrying out nursing care on three patients. The results before being given therapy were the average temperature of patient 1 (38.10c), patient 2 (38.00c) and patient 3 (37.90c). After being given vera compress therapy, the results were the average body temperature of patient 1 (35, 70c), patient 2 (35.70c) and patient 3 (36.30c), so it showed that the application of aloe vera compress therapy had proven effective in reducing body temperature in children with fever. Conclusion: Children with fever need to be treated immediately. Therefore, the main thing that can be done is non-pharmacological therapy, such as aloe vera compress therapy, because aloe vera has a water content of 95%, lignin and saponin, which reduce body temperature and other methods. The heat transfer method used is through conduction and evaporation.